On the reliable generation of 3D city models from open data - Girindran, Renoy (2021)
The battle for sustainability will be won or lost in cities. Currently more than 50% of the World’s population reside in urban areas and this figure is estimated to reach 68% by 2050. New and innovative approaches are needed for managing urban areas and this demands the generation of appropriate data for evidence-based decision making. Geospatial technologies play an important role in meeting this demand and it is evident that 3D geospatial data of cities provide richer intelligence than 2D geospatial data. However, presently, there is a dearth of free, high-resolution 3D city models available for use especially in developing and underdeveloped countries, which, it could be argued, is where these data are most required.